Verskyning en verdwyning van 'n verligte mens 'n Boeddha in Theravāda perspektief, mistiek vertolk - Krüger, .S (HTS Religion & Society Series, 2022)
The book offers an Afrikaans translation (in six chapters) of selected parts of a number of Pali suttas dealing with the birth of a previous Buddha (Vipassi); a previous life of the 'present' Buddha (Siddhattha Gotama), his enlightenment experience, and his death; the appearance of the next Buddha (Metteya); and the phenomenon of a 'silent' (pacceka) Buddha. Standard books on the life of the Buddha usually restrict themselves to probable historical reconstructions of his life and times, with a cursory interest in the role and significance of myth in the Buddha pictures. The proposed new book focuses on the role of myth and seeks to plumb the mythological context. This opens a new window on a comparative study of the Buddha and, for example, the mythological encapsulation of the Jesus phenomenon in a thought experiment of a millennium, finding its apex in the High Scholasticism of Thomas of Aquinas. The book seeks to focus on the different ways in which traditional orthodox Christianity sought, and seeks, to reconcile theory and mythology and on the manner in which this important dimension was dealt with in Buddhism.